Are We Learning Enough Pathology in Medical School to Prepare Us for Postgraduate Training and Examinations?. (27th February 2013) - Marsdin, Emma; Biswas, Seema
Abstract : Medical schools responded to the first publication of Tomorrow's Doctors with an abbreviated syllabus and a reduction in didactic teaching hours. Prescribing errors, however, have increased, and there is a perception amongst clinicians that junior doctors know less about the pathological basis of disease. We asked junior doctors how useful they thought their undergraduate teaching in pathology had been in their postgraduate training. We had 70 questionnaire responses from junior doctors within a single deanery and found that although almost every doctor, n = 61 (96%), thought that pathology formed a major component of their postgraduate exams, most, n = 47 (67%), thought that their undergraduate teaching left them unprepared for their postgraduate careers, and they had to learn basic principles, as they revised for postgraduate exams. Few used a pathology text for learning, most doctors, n = 64 (91%), relying on question and answer revision resources for exam preparation. Perhaps, as revision materials are used so widely, they might be adapted for long-term deep learning, alongside clinical work. This presents an opportunity for pathologists, deaneries, royal colleges, and publishing houses to work together in the preparation of quality written and online material readily accessible to junior doctors in their workplace.